Comparative Effects of Physical Exercise and Other Behavioral Interventions on Functional Status Outcomes in Mild Cognitive Impairment. (26th September 2021) - Shandera-Ochsner, Anne L.; Chandler, Melanie J.; Locke, Dona E.; Ball, Colleen T.; Crook, Julia E.; Phatak, Vaishali S.; Smith, Glenn E.
Abstract: Objectives: : Lifestyle modifications for those with mild cognitive impairment (MCI) may promote functional stability, lesson disease severity, and improve well-being outcomes such as quality of life. The current analysis of our larger comparative effectiveness study evaluated which specific combinations of lifestyle modifications offered as part of the Mayo Clinic Healthy Action to Benefit Independence in Thinking (HABIT) program contributed to the least functional decline in people with MCI (pwMCI) over 18 months. Methods: : We undertook to compare evidence-based interventions with one another rather than to a no-treatment control group. The interventions were five behavioral treatments: computerized cognitive training (CCT), yoga, Memory Support System (MSS) training, peer support group (SG), and wellness education (WE), each delivered to both pwMCI and care partners, in a group-based program. To compare interventions, we randomly withheld one of the five HABIT® interventions in each of the group sessions. We conducted 24 group sessions with between 8 and 20 pwMCI–partner dyads in a session. Results: : Withholding yoga led to the greatest declines in functional ability as measured by the Functional Activities Questionnaire and Clinical Dementia Rating. In addition, memory compensation (calendar) training and cognitive exercise appeared to have associations (moderate effect sizes) with better functional outcomes. Withholding SG or WE appeared to have little effect on functioning at 18 months. Conclusions: : Overall, these results add to the growing literature that physical exercise can play a significant and lasting role in modifying outcomes in a host of medical conditions, including neurodegenerative diseases.